Predictors of the Size and Surgical Freedom of the Trans-Cribriform and Trans-Clival Corridors, a Radiographic Analysis - Aljuboori, Zaid; Nuru, Mohammed; Sharma, Mayur; Andaluz, Norberto (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction The transcribriform and transclival corridors are endoscopic endonasal approaches used to treat pathologies of the skull base. We present a predictive model that uses the clival length and ethmoidal width to predict the size and surgical freedom (SF) of these corridors.Methods Adult facial computed tomography scans were reviewed. Exclusion criteria included patients <18 years of age or radiographic evidence of trauma, neoplasm, or congenital deformities of the skull base. The images were analyzed using OsiriX MD (Bernex, Switzerland). Patients' demographics, clival length, ethmoidal width, surface area, and others were collected. Linear regression was used to create prediction models for the size and SF of the transclival and transcribriform corridors.Results A total of 103 patients were included with an average age of 44.9 years and 47% males. Females had a smaller clival surface area (8 vs. 9.2 cm2, p = 0.001). For transclival corridor, clival length correlated positively with SF in the sagittal plane (rho = 0.44, p < 0.05) and negatively with SF in the coronal plane (rho = − 0.2, p < 0.05). For transcribriform corridor, ethmoidal width correlated positively with SF in the coronal plane (rho = 0.74, p < 0.05), and negatively with SF in the sagittal plane (rho = − 0.2, p < 0.05).Conclusion A significant variability of the bony anatomy of the anterior and central skull base was found. The use of clival length and ethmoidal width as part of preoperative surgical planning might help to overcome the anatomical variability which could affect the adequacy of surgical corridors.
Keywords: skull base; approaches; transcribriform; endoscopic; transclival